If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -4) = -16 Reorder the terms: -2(-4 + x) = -16 (-4 * -2 + x * -2) = -16 (8 + -2x) = -16 Solving 8 + -2x = -16 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -2x = -16 + -8 Combine like terms: 8 + -8 = 0 0 + -2x = -16 + -8 -2x = -16 + -8 Combine like terms: -16 + -8 = -24 -2x = -24 Divide each side by '-2'. x = 12 Simplifying x = 12
| x+4=6x-6 | | 0=3x-9-4x | | 5x+-3=-18 | | 14+8a=4a-10 | | X+3y=60 | | 7c+28=105 | | 16x-9x-15=13 | | 4c-13c-6c=-49 | | 35x^2y^2+9xy+-2=0 | | 2(6w-9)-6=24-12w | | 5x-2=15x+112 | | 5-2z=17 | | 15r+6s-11t+r-9s+t-2s+5r-2t-r= | | 4+x+7=-36 | | 28-0.3y=0.7t-12 | | x=16+3y | | 35(x^2)*(y^2)+9xy-2=0 | | x^4-9x^3+18x^3=0 | | x+4+7=-36 | | 5a-4(3a+7)=-221 | | 9(x-4)=-3x+96 | | 3p-12=12+15p | | 10-(-25)=d | | 10w-3=8w | | 6d-4=2(5d-2) | | 21(x^2)*(y^2)+11xy-2=0 | | A=bxt+g | | 112+x=105 | | 18-6a=4a-4(a+13) | | 3x+17=98 | | 3*-24/8=1/5(2*-24+3) | | -15-20=c |